Preparation of Strawberry Jam and Estimation of its Nutritive Value during Storage - Rahman , M Moshiur (Journal of Postharvest Technology, 2018)
The processing of jam from strawberry was studied during storage and found successful from the sensory evaluation the mean score showed that T2 (pulp to sugar ratio 1:1.25) was most preferred considering all the characters as colour, flavour, sweetness and overall acceptability followed by T1. After 2, 4 and 6 month of storage the moisture content had slightly increased. The initial TSS and total sugar content of strawberry jam were maximum in T3 (67.25 % and 41.50 %, respectively) while these were minimum in T1 (66.12 % and 40.07 %, respectively). This study revealed at the end of storage 0.29 to 1.00 % TSS and 5.14 to 5.89 % total sugar were reduced. At initial stage titratable acidity and pH level were found higher in T1 (0.65 % and 2.81, respectively) and at the end of 6 months of storage titratable acidity and pH of this treatment were 0.69 % and 2.78, respectively. Ascorbic acid content of strawberry jam was found very low (14.75-17.49 mg 100 g-1). This study revealed ascorbic acid content of strawberry jam decreased during storage. After 6 month of storage the maximum reduction of ascorbic acid was noted in T3 (14.44 %), while minimum in T2 (11.06 %). Just after cooking β-carotene content of strawberry jam was found higher at T1 (1.81 μg 100 g-1), and at the end of storage period it was 1.69 μg 100 g-1. During 6 months of storage, maximum reduction of β-carotene was recorded in T1 (6.6 %), while minimum in (3.5 %) from T3. Considering sensory evolution, nutrients content and storage study jam prepared form 1:1.25 pulp to sugar ratio i.e.T2 formulation was found better.